2019
DOI: 10.1096/fj.201900665rr
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates the protective effects of dietary β‐hydroxy‐β‐methylbutyrate (HMB) against obesity induced by high‐fat diets

Abstract: Obesity increases the risk of developing insulin resistance and diabetes and is a major public health concern. Our previous study shows that dietary β‐hydroxy‐β‐methylbutyrate (HMB) improves lipid metabolism in a pig model. However, it remains unclear whether HMB blocks obesity through gut microbiota. In this study, we found that HMB reduced body weight, alleviated the whitening of brown adipose tissue, and improved insulin resistance in mice fed a high‐fat diet (HFD). High‐throughput pyrosequencing of the 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 63 publications
13
54
0
Order By: Relevance
“…The key to understanding obesity may be related to changes in the gut microbiota and its function in response to diet [26]. Several studies confirm that in both human and rat models, the gut microbiota in obesity exhibits greater relative abundance of Firmicutes and decreased levels of Bacteroidetes [27][28][29]. In line with these findings, this study found relative changes in the gut microbiota of HFD mice, showing that kaempferol supplementation led to lower levels of Firmicutes and higher levels of Bacteroidetes.…”
Section: Discussionsupporting
confidence: 82%
“…The key to understanding obesity may be related to changes in the gut microbiota and its function in response to diet [26]. Several studies confirm that in both human and rat models, the gut microbiota in obesity exhibits greater relative abundance of Firmicutes and decreased levels of Bacteroidetes [27][28][29]. In line with these findings, this study found relative changes in the gut microbiota of HFD mice, showing that kaempferol supplementation led to lower levels of Firmicutes and higher levels of Bacteroidetes.…”
Section: Discussionsupporting
confidence: 82%
“…38,39 Analysis of fecal samples of type 2 diabetes patients revealed reductions of gut microbiota diversity and abundance of butyrate-producing bacteria (eg, Roseburia, Faecalibacterium prausnitzii), and increased levels of certain conditionally pathogenic bacteria such as Escherichia coli. 38,39 Analysis of fecal samples of type 2 diabetes patients revealed reductions of gut microbiota diversity and abundance of butyrate-producing bacteria (eg, Roseburia, Faecalibacterium prausnitzii), and increased levels of certain conditionally pathogenic bacteria such as Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…The gut microbiota have been identified as an environmental factor that markedly affects digestive capacity, nutritional absorption, energy balance, and body fat accumulation in mammals. [81][82][83][84] Germ-free animal and fecal microbial transplantation provide direct insights into the function of gut microbiota in host lipid metabolism and obesity development. Germ-free mice fail to gain additional weight and remain lean compared to conventionally raised counterparts.…”
Section: Gut Microbiotamentioning
confidence: 99%